FACTORS IMPACTING THE CONTINUED USE OF SOCIAL MEDIA: A CASE STUDY OF SENIOR CITIZENS IN BANGKOK - Deeananlarp, Yanisa; Nuangjamnong, Chompu; Dowpiset, Kitikorn (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Abstract This study aimed to identify the factors affecting senior citizen users of social media in Bangkok, Thailand. The proposed of this research is also to determine the impact of user satisfaction on the continued use of social media. This study is quantitative research with several testing such as Cronbach’s Alpha, Descriptive and Inferential Statistics to assess the reliability of the questionnaire analyze demographic information and testing the hypotheses. The surveys were distributed 400 sets to sample who are over 60 years old, live in Bangkok, and have used social media. The study results were the factor affecting on user satisfaction are utilitarian benefits and hedonic benefits at a significant level of 0.05, and further impacts continued use. Keywords: Utilitarian benefits, Hedonic benefits, User satisfaction, Continued use, Social media, Senior citizen.